1999
DOI: 10.1089/088922299310566
|View full text |Cite
|
Sign up to set email alerts
|

Aminooxypentane-RANTES, an Inhibitor of R5 Human Immunodeficiency Virus Type 1, Increases the Interferon gamma to Interleukin 10 Ratio without Impairing Cellular Proliferation

Abstract: Studies have demonstrated that the beta-chemokines RANTES, MIP-1alpha, and MIP-1beta suppress human immunodeficiency type 1 (HIV-1) replication in vitro. Infection with HIV-1 requires expression of CD4 antigen and the chemokine receptor CXCR4 (X4) or CCR5 (R5) on the surface of target cells. The engagement of these receptors with the viral surface proteins is essential for the membrane fusion process. This study investigated the anti-HIV-1 activity of a derivative of RANTES, the CCR5 antagonist aminooxypentane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Since Pf-gp6 did not interfere with the binding of anti-CCR5 or anti-CXCR-4 mAb to the host cells, the substance is considered not to be a co-receptor antagonist. The inhibition of anti-chemokine receptor mAb binding has been reported on bicyclams (Schols et al, 1997), TAK-779 (Dragic et al, 2000), aminooxypentane-RANTES (Rusconi et al, 1999) and ALX40-4C (Doranz et al, 1997); however, they were found to be co-receptor antagonists. Another inhibitor similar to Pf-gp6 is a lipophosphoglycan from Leishmania (Martin et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Since Pf-gp6 did not interfere with the binding of anti-CCR5 or anti-CXCR-4 mAb to the host cells, the substance is considered not to be a co-receptor antagonist. The inhibition of anti-chemokine receptor mAb binding has been reported on bicyclams (Schols et al, 1997), TAK-779 (Dragic et al, 2000), aminooxypentane-RANTES (Rusconi et al, 1999) and ALX40-4C (Doranz et al, 1997); however, they were found to be co-receptor antagonists. Another inhibitor similar to Pf-gp6 is a lipophosphoglycan from Leishmania (Martin et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…For example, chemokine RANTES features a Ser residue on the N-terminus. Periodate oxidation of RANTES followed by oxime bond formation with aminooxypentane generated aminooxypentane (AOP)-RANTES, a potent inhibitor of infection of diverse cell types by HIV-1. This RANTES analogue was also produced by total chemical synthesis …”
Section: Glyoxylyl Group: Synthetic Methodsmentioning
confidence: 99%
“…Other medical areas have also benefited from glyoxylyl chemistry. A seminal contribution to the field is the design of chemokine RANTES analogues as anti-HIV agents. …”
Section: Introductionmentioning
confidence: 99%
“…Modified chemokines such as amino-oxypentane-RANTES (AOP-RANTES) and N-nonanoyl-RANTES (NNY-RANTES) efficiently bind to their own receptors and frequently show enhanced anti-HIV effects together with a decreased proinflammatory activity [50,[59][60][61]. Alternatively, RANTES has been used in combination with glycosaminoglycans, to reduce its proinflammatory activity [62] and still retaining the ability of inhibiting HIV replication [63]. A different approach could exploit the recent paradigm of viral decoy chemokines [64][65][66] and chemokine receptors [67], or engineering small peptides mimicking the N-terminus of CCR5 that have been shown to inhibit HIV in vitro [68].…”
Section: Chemokines Chemokine Homo-logues and Entry Coreceptor Inhi-mentioning
confidence: 99%